KOMUNITAS RERESIK SAMPAH VISUAL: MEMBANGUN KESADARAN BARU TATA VISUAL IKLAN MEDIA LUAR GRIYA DI YOGYAKARTA - Hesti Rahayu (Institut Seni Indonesia Yogyakarta, 2014)
The subject of this research is the Reresik Sampah Visual (RSV) community, its efforts andactivities in building new awareness of Yogyakarta people about the importance of a visual managementshould be applied to the out of home (OOH) advertising in Yogyakarta. New awareness will result in a newculture; a culture that is more environmentally friendly. It is hoped that this culture will finally restore theaesthetic and visual management of the OOH advertising that is more comfortable for the public.A qualitative method of research is employed to descriptively analyze the data gathered from observations,interviews, documentations and library study.To gain its objective, the RSV community incessantly campaigns its opinions based on the Five Percepts ofRSV. The opinions are buzzed by raiding the OOH ads placed on streets, forming community via socialmedia networking, writing on the mass media, and undertaking discussion forums. The RSV activity is alocal movement that is similar to the New Social Movement fighting for the improvement of the quality oflife and focuses on the non economy redistribution and non violence issues.Keywords: Community, Reresik Sampah Visual, Visual management, New awareness, Out of homeAdvertising.